Post-operative re-irradiation with hyperthermia in locoregional breast cancer recurrence: Temperature matters. (February 2022) - Bakker, Akke; Tello Valverde, C. Paola; van Tienhoven, Geertjan; Kolff, M. Willemijn; Kok, H. Petra; Slotman, Ben J.; Konings, Inge R.H.M.; Oei, Arlene L.; Oldenburg, Hester S.A.; Rutgers, Emiel J.T.; Rasch, Coen R.N.; van den Bongard, H.J.G. Desirée; et al.
Highlights: Postoperative re-irradiation and hyperthermia is effective in recurrent breast cancer. CEM43T50 incorporates both hyperthermia treatment duration and median temperature. Thermal dose CEM43T50 was significantly associated with better locoregional control. Three-year locoregional control was 92% vs. 74% for high vs. low thermal dose group. Grade 3-4 late toxicity was similar for the low and high thermal dose subgroups. Abstract: Purpose: To investigate the impact of hyperthermia thermal dose (TD) on locoregional control (LRC), overall survival (OS) and toxicity in locoregional recurrent breast cancer patients treated with postoperative re-irradiation and hyperthermia. Methods: In this retrospective study, 112 women with resected locoregional recurrent breast cancer treated in 2010–2017 with postoperative re-irradiation 8frx4Gy ( n  = 34) or 23frx2Gy ( n  = 78), combined with 4–5 weekly hyperthermia sessions guided by invasive thermometry, were subdivided into 'low' ( n  = 56) and 'high' TD ( n  = 56) groups by the best session with highest median cumulative equivalent minutes at 43 °C (Best CEM43T50) < 7.2 min and ≥7.2 min, respectively. Actuarial LRC, OS and late toxicity incidence were analyzed. Backward multivariable Cox regression and inverse probability weighting (IPW) analysis were performed. Results: TD subgroups showed no significant differences in patient/treatment characteristics. Median follow-up was 43 months (range 1–107 months). High vs. low TD was associated with LRC ( p  = 0.0013), but not with OS ( p  = 0.29) or late toxicity ( p  = 0.58). Three-year LRC was 74.0% vs. 92.3% in the low and high TD group, respectively ( p  = 0.008). After three years, 25.0% and 0.9% of the patients had late toxicity grade 3 and 4, respectively. Multivariable analysis showed that distant metastasis (HR 17.6; 95%CI 5.2–60.2), lymph node involvement (HR 2.9; 95%CI 1.2–7.2), recurrence site (chest wall vs. breast; HR 4.6; 95%CI 1.8–11.6) and TD (low vs. high; HR 4.1; 95%CI 1.4–11.5) were associated with LRC. TD was associated with LRC in IPW analysis ( p  = 0.0018). Conclusions: High thermal dose (best CEM43T50 ≥ 7.2 min) was associated with significantly higher LRC for patients with locoregional recurrent breast cancer treated with postoperative re-irradiation and hyperthermia, without augmenting toxicity.